Kemampuan Pemecahan Masalah Dalam Menyelesaikan Soal Volume Kubus - Yeni Dwi Kurino; Tatang Herman; Turmudi; Wahyudin; Ani Rosidah; Dudu Suhandi Saputra (Jurnal Elementaria Edukasia, 2023)
Problem solving ability is an ability that every student should be able to master so that the learning process runs smoothly. In problem solving, students are expected to have the ability to understand concepts, solve problems and be able to relate concepts to each other. The ability to understand problems must be related to students' daily lives, so that students can easily and longer remember the material given by the teacher. The aim of this research is to analyze the problem solving abilities faced by each student in solving volume cube problems. This type of research is qualitative research with qualitative descriptive methods. Subject selection was carried out using the Purposive Sampling method and 6 students were obtained as research subjects. Data collection was carried out using test and non-test methods, for the test students were given questions in the form of cube volume questions and for the non-test interviews and observations were carried out. Based on the research results, it shows that students who have high problem solving abilities almost master all indicators of problem solving abilities because there is only 1 indicator that students lack mastery, namely the indicator of solving problems with a plan. Students who fall into the category of moderate problem solving ability are able to understand problems and formulate plans but are still considered lacking in problem solving ability because there are several indicators that one of the students lacks control over, namely understanding problems and solving problems with a plan. Students who fall into the low problem solving ability category are considered to be lacking in problem solving ability because they lack mastery of each indicator, namely understanding problems, preparing plans, implementing plans, and looking back.